Antimicrobial effectiveness of intracanal medicaments on Enterococcus faecalis: chlorhexidine versus octenidine. (30th June 2012) - de, J. M. V. M.; Decker, E. M.; Walter, C.; Boeira, L. S.; Löst, C.; Weiger, R.
Abstract Aim To determine the viability of Enterococcus faecalis in infected human root dentine in vitro after exposure to root canal medicaments based on chlorhexidine and octenidine. Methodology Human root segments (n = 40) were infected with E. faecalis for 8 weeks. Root dentine samples (rd) collected at week 4 served as individual baseline values. At week 8, the root segments were randomly divided into four test groups (n = 10 each) for the placement of one of the following medicaments in the root canals: calcium hydroxide paste (CH), chlorhexidine gel (CHX‐gel) (5.0%), chlorhexidine/gutta‐percha points (CHX‐GP) (active points®; Roeko, Langenau, Germany) and octenidine gel (OCT‐gel) (5.0%) followed by incubation for 4 weeks. The effect on E. faecalis viability was assessed by two fluorescent dyes (syto 9/propidium iodide) to determine the 'proportion of viable bacteria' (PVB%) and number of 'colony‐forming units' (CFU). Mean values and 95% confidence intervals (CI) were calculated for PVB% and log CFU, and the difference between groups was established. Results Viable and dead bacterial cells were detected in all 'rd' samples at weeks 4 and 8. The treatment with CHX‐gel, CHX‐GP and OCT‐gel resulted in significantly lower PVB% values with 15.4%, 3.5% and 0%, respectively. No growth (CFU) was recorded for these samples at week 12. When medicated by CH, the PVB% was increased without a corresponding change in CFUs. Conclusions In contrast to calcium hydroxide, both CHX – and octenidine‐based intracanal medicaments were effective in decreasing the viability of E. faecalis. OCT showed the most favourable results and may have potential as an endodontic medicament.